Donepezil, an Acetylcholinesterase Inhibitor, Can Attenuate Gabapentinoid-Induced Somnolence in Patients with Neuropathic Pain: A Retrospective Chart Review. (2nd January 2017) - Kogure, Takamichi; Sumitani, Masahiko; Ikegami, Kiyoshi; Abe, Hiroaki; Hozumi, Jun; Inoue, Reo; Kawahara, Kazuo; Yamada, Yoshitsugu
ABSTRACT: Donepezil, an oral acetylcholinesterase inhibitor, is used to treat Alzheimer's disease and reportedly attenuates opioid-induced sedation in patients with cancer pain. Neuropathic pain is often treated with gabapentinoids (pregabalin, gabapentin), but gabapentinoid-induced somnolence sometimes prevents patients from using these agents. We conducted a retrospective chart review of patients with neuropathic pain to examine whether donepezil is useful for gabapentinoid-induced somnolence. We investigated pain severity in 13 patients before and after taking gabapentinoids and donepezil, the degree of gabapentinoid-induced somnolence before and after starting donepezil, and gabapentinoid dose escalation after taking donepezil. Donepezil was started at 3–5 mg/day upon experiencing gabapentinoid-induced somnolence. Likert-scale scores for somnolence (0 = no somnolence ; 4 = severe somnolence with stumbling ) improved significantly after starting donepezil (before: 2.3 ± 0.9, after: 0.5 ± 0.7; Wilcoxon's signed-rank test, P < .05), resulting in gabapentinoid dose escalation (before: 796.2 ± 564.3 mg, after: 1409.6 ± 526.9 mg; P < .05), which significantly decreased pain intensity (before: 7.4 ± 1.2, after: 5.0 ± 1.3; P < .05). Donepezil could be an alternative to psychostimulants for gabapentinoid-induced somnolence. The analgesic effect of gabapentinoids remained uncompromised by donepezil, which could enhance the dose-dependent analgesic effect of gabapentinoids.